Transhumanism - Huxley, Julian (ETHICS IN PROGRESS, 2015)
In his famous paper, Julian Huxley gives the outline of what he believes future humanity could – and should – look like. By pointing out the numerous limitations and feebleness the human nature is – at the time – prone to, and by confronting them with the possibilities humankind has, Huxley expresses the need to research and put into use all possible measures that would enable man achieve utmost perfection.